(untitled) (Palíndromo, 2015)
The catharsis is considered by many scholars as an “effect” tied to a process which leads to awareness. From this premise, the article on the screen want to revisit the concept of Catharsis from Aristotle, Vygotsky, Jauss and, in parti- cular, Georg Lukács. Search approach the ideas of Lukács, related to catharsis, the field of education, in particular the teaching of art, both at school and in the exhibition space.